Manajemen Kepala Sekolah Guna Meningkatkan Mutu Pendidikan di SMA N 1 Indramayu - Fuaidiah, Millatul (Lembaga Riset Ilmiah, 2023)
The background of this research is due to changes in science and technology which are developing rapidly and bringing many changes in various aspects of life. Education today must be able to adapt to changes according to the era. For this reason, the reliability of the Principal's Management is needed in improving the quality of Education. The progress of education in schools is greatly influenced by the ability of the principal in managing each component of the school. As well as the ability of the principal related to understanding and knowledge of management and the tasks that must be carried out. Principals need to carry out quality and dynamic interactions with teachers, administrative staff, and students who play a very important role, especially in adjusting various school activities to the demands of globalization, societal changes, developments in science and technology. The approach to this research method is descriptive qualitative with a case study approach, the analysis used by researchers is data triangulation. made a new breakthrough by integrating several elements of the curriculum, namely the Salaf School component, the modern boarding school component of the Gontor Modern Islamic Boarding School and the Ministry of Education and Culture's National Curriculum. This is done to improve the quality of education and respond to global challenges.